Clinical services assessment and reengineering: lessons learned...Proceedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston, TX, May 6-9, 1999 - Lyche DK; Richardson RR Jr.; Maliff RP; Romlein J; Norton GS (Journal of Digital Imaging)
Healthcare enterprises often 'acquire and install' picture archiving and communications systems (PACS) without examining many of the care delivery processes and information flows that will be affected. Many times these unexamined factors can delay or be the cause of failure of the PACS project. This article presents issues that were worked through as part of a PACS clinical services assessment and reengineering analysis for several US military medical treatment facilities. Copyright (c) 1999 by W.B. Saunders Company